2000
DOI: 10.1080/10610270008049128
|View full text |Cite
|
Sign up to set email alerts
|

A Complex between C-Methylcalix[4]resorcinarene and Triethylammonium Nitrate

Abstract: The synthesis and crystal structure of the complex formed by the all-cis epimer of C-methylcalix[4lre-sorcinarene (1) and triethylammonium nitrate are reported. "1.(HNEt:)4 . (NO; )1(2)", crystallizes in the monoclinic space group PZ1/n, a= 25.796(2), b= 16.6048(1!), c= 29.5659(10) A, / I = 94.636(4)', V= 12623(2) A', Z= 8. Refinement led to a final conventional R1 value of 0.128 for 12428 reflections and 1473parameters. The resorcinarene displays the usual bowl-type shape, with four hydroxyl protons involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…36 In this assembly, the protonated -NH is directly hydrogen bonded to the hydroxyl groups of the resorcinarenes (NH⋯O), leading to a pseudocapsular dimeric assembly. 36 Despite the multitude of reported structures involving quaternary ammonium salts and unfunctionalized resorcinarenes and pyrogallarenes, there are limited reports on hostguest complexes with primary 30 and tertiary 35,[37][38][39] ammonium cations. Host-guest complexes of unfunctionalized resorcinarenes and secondary ammonium cations are very poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…36 In this assembly, the protonated -NH is directly hydrogen bonded to the hydroxyl groups of the resorcinarenes (NH⋯O), leading to a pseudocapsular dimeric assembly. 36 Despite the multitude of reported structures involving quaternary ammonium salts and unfunctionalized resorcinarenes and pyrogallarenes, there are limited reports on hostguest complexes with primary 30 and tertiary 35,[37][38][39] ammonium cations. Host-guest complexes of unfunctionalized resorcinarenes and secondary ammonium cations are very poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…C-Methylcalix[4]resorcinarene (Figure ), hereafter abbreviated CAL-Me, is the simplest member of the resorcinarene compounds. A solid-state structure of CAL-Me cocrystallized with various small molecules, e.g., solvents, has been exclusively studied using X-ray crystallography. , Recent X-ray diffraction studies showed a dramatic effect of water and CH 3 CN exerted on C-alkylpyrogallol[4]arene assemblies by means of intermolecular hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%